THERAPEUTIC STRATEGY IN THE REHABILITATION OF THE DYSPLASTIC HIP THROUGH ARTHROPLASTY - Liliana SAVIN; C BARBĂROȘIE (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2012)
Total hip arthroplasty in degenerative pathology secondary to congenital dysplasia differentiates itself amongtotal arthroplasties by the frequent technical difficulties it poses and the site where it is performed. The existence of aform of congenital dysplasia that remained untreated or insufficiently treated in childhood leads to irreversibledeformities in adulthood. Partial or total loss of joint congruence causes, in time, degenerative changes with theimpairment of hip mobility and is associated with a number of progressive deformations (limb length discrepancy,abnormal rotation, asymmetric lesions, periarticular muscle failure), which gradually reduce the quality of the patient'slife. This study aims at investigating the incidence of prosthetic hip arthroplasty for osteoarthritis secondary todysplastic hip in the total number of arthroplasties, the age when surgery is performed, the type of deformity andprosthetic components used, and the postoperative and long-term functional results. The study was conducted on 110patients who received total hip arthroplasty due to osteoarthritis secondary to hip dysplasia, between 1994 and 2011, inthe Orthopaedics Trauma Department of the Rehabilitation Hospital of Iasi, the incidence being of 3.34% of the totalnumber of arthroplasties, with a prevalence of 65% under the age of 50 years. The functional results were assessed,according to the Harris-hip-score parameters, as good or very good in proportion of 82%. The complexity of the areawhere the total hip arthroplasty is performed requires a good management consisting of thorough preoperativeplanning, determining the operatory indication, and specialized and individualized medical recovery.